Physics and Chemical Characteristics of Sargassum Sp. Seaweed with Addition of Sodium Alginate Stabilizer to Different Concentrations. (February 2019) - Via, M; Abdillah, A A; Alamsjah, M A
Abstract: One of the most effective ways to increase the use of the Sargassum seaweed resources in Indonesia is by processing them into syrup products. Syrup is a fast-food beverage product and is easily dissolved in water which makes it practically easy to serve. It could also be saved relatively long. Additional ingredients that could stabilize or bind the processed products can be developed using Sargassum seaweed. Sargassum seaweed contains phenol compounds and polysaccharides in the form of alginate which functions as a thickening and gelling agent. . This study aims to determine the physical and chemical characteristics of Sargassum sp. Which was given different concentration level of sodium alginate as stabilizer. The results of the Analysis of Variance (ANOVA) showed that the administration of alginate and CMC type stabilizers gave significant differences (p <0.05) on the viscosity parameters, total plate numbers, and organoleptic parameters in the form of taste and texture. Meanwhile the color parameters and the aroma did not show any effect. Statistical test results showed that the CMC type or control treatment was able to maintain the sweetness level with an average score of 4.8. The viscosity test showed that the treatment with the administration of 1% sodium alginate stabilizer or P3 resulted in the highest average viscosity value which was 139.60 Cps.